Dancing with(in) possibilities: emerging public and convivial pedagogies for ecological citizenship - Skerritt, Hayley Frances (Rhodes University, Faculty of Education, Department of Secondary and Post School Education)
This research project explores ways in which ecological citizenship can be stimulated through collaborative public pedagogy and transgressive learning (t-learning) processes. This research identifies 'places' of innovation to cover sections that would usually be described in terms of 'problem statement', 'research focus', 'intended outcomes / main contribution' and 'theory and methodology'. The Place of Worry is identified through the triple C Crisis (Covid, Capitalism and Climate-Change) which reveal the disconnect to the diverse ecologies (both social and natural) that sustain us. The Place of Possibility demonstrates that through ecological citizenship we can begin to absent absences (De Sousa Santos, 2016) and transform into an embodied response to the triple C crisis. The Place of Emergence transforms these possibilities into practice by demonstrating the place between the worry and the possibility allows for an emergence of a new kind of solution, referred to as the third space within this thesis. The Place of Process delves into the t-learning stories that emerged through research creation and works with iterative feedback and cycles of creation. The unfolding of this t-learning project is guided by the use of metaphor and symbolism as a figuration of macro- and microscopic interactions within these learning fields/ecosystems. Symbolic figuration and speculative metaphor are valuable in this thesis and in my own collaborative meaning-making endeavour as they offer translation protocols for when language fails to embody, the rich embodied experience of this form of learning. The embodiment of this work will help to create restorative care practices through transgressive learning (Lotz-Sisitka et al., 2016) and research creation (Manning, 2016). The study has a particular focus on the emergence of identities and onto-epistemological orientation within the social learning journey towards ecological citizenship and the various ways in which they can be embodied to enable public pedagogy.
Keywords: Environmental education; Environmental responsibility; Environmental protection -- Citizen participation; Transformative learning; Creation (Literary, artistic, etc.)